Comments and records on the large branchiopod Crustacea (Anostraca, Notostraca, Laevicaudata, Spinicaudata, Cyclestherida) of the Neotropical and Antarctic bioregions. (2nd January 2021) - Rogers, D. Christopher; Severo-Neto, Francisco; Volcan, Matheus Vieira; De los Ríos, Patricio; Epele, Luis B.; Ferreira, Aloisio O.; Rabet, Nicolas
ABSTRACT: The large branchiopod crustacean fauna (fairy shrimp, tadpole shrimp and clam shrimp) of the Neotropical Bioregion are incompletely known, with scattered records for many taxa, and many new taxa discovered and described regularly. As an aid to furthering our knowledge of the group in this region, we present an assortment of notes and records on various Neotropical taxa. We present our information in the form of a checklist, listing all reported species, with a review of their known distribution, with 56 new distributional records for 29 taxa. We also include a revised description of Spiralifrons mira based on new material from Brazil, and provide important comments on the Leptestheriidae, reducing Strakrabiidae, Straskrabia, and Brtekia to synonymy. The information presented here will assist in additional studies, surveys, and conservation, as well as help develop a biogeographical understanding of this vast region. Thus, we have compiled these records so that it will be available to other researchers. Future survey efforts will undoubtedly reveal additional records and taxa.